Flutuação populacional de lagartas desfolhadoras e distribuição espacial de Plusiinae na cultura da soja [Glycine Max (L.) Merril] - Oliveira, Tiago Carvalhais de (2014)
Caterpillars defoliators of soybean occurs in different times and feed on different parts of the plant, mainly in flowers and pods. During the growing seasons of 2011/2012 and 2012/2013, soybean fields were sampled in different crop phenological stages with the objective of knowing the population fluctuation of the main species of caterpillar defoliating soybeans and to determine the within field spatial distribution of the species of the Plusiinae complex, to describe how species colonize the soybean field. Five commercial fields submitted to different management practices were monitored. Sampling meshes were fabricated with equidistant points 50 meters. The areas were sampled weekly from the occurrence of the first defoliating caterpillars, until close to harvest. The sampling method used was ground cloth, with one row-meter. It was quantified all caterpillars. Data were submitted to statistical analysis using the following SAS procedures: Proc Univariate, Proc Means, Proc Freq. To test what statistical distribution fit to caterpillars population the procedure Proc Genmode was used. Maps representing the localization of samples of caterpillars in soybean fields were constructed. The species of Plusiinae predominated in the area, corresponding to 52, 04% in 2011/2012 e 48, 53% in 2012/2013 of the total of caterpillars found in the reproductive phase of soybean. The distribution of the complex of Plusiinae within field is random and do not present border effect. In this study, while the population fits the negative binomial distribution maps clearly indicate that the caterpillars are randomly dispersed in soybean fields.